Comparative Analysis of Personal Data Protection Laws in Indonesia and Thailand: A Legal Framework Perspective - Lu Sudirman; Hari Sutra Disemadi; Arwa Meida Aninda (JED (Jurnal Etika Demokrasi), 2023)
The existence of violations of personal data remains a legal issue at present. The protection of personal data is of utmost importance, serving not only as a safeguard but also as the foundation for comprehensive regulations concerning personal data. This research aims to compare regulations on personal data protection between Indonesia and Thailand, with a particular emphasis on human rights aspects. The research methodology used is normative legal research. The findings of this study reveal that both Indonesia and Thailand recognize that personal data protection is an integral part of human rights. This acknowledgment is reflected in their respective constitutions and various applicable laws. Indonesia recently enacted specific legislation on personal data protection in 2022, but its implementation still faces various challenges. The results of this research indicate that while both countries recognize the significance of personal data protection as a component of human rights, there are significant differences in their approaches and implementations between Indonesia and Thailand.